2018
DOI: 10.1371/journal.pone.0195241
|View full text |Cite
|
Sign up to set email alerts
|

The endangered Florida pondweed (Potamogeton floridanus) is a hybrid: Why we need to understand biodiversity thoroughly

Abstract: Thorough understanding of biodiversity is a fundamental prerequisite for biological research. A lack of taxonomic knowledge and species misidentifications are particularly critical for conservation. Here we present an example of Potamogeton floridanus, the Florida Pondweed, an endangered taxon endemic to a small area in the Florida panhandle, whose taxonomic status remained controversial for more than a century, and all previous attempts to elucidate its identity have failed. We applied molecular approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Due to the heterosis effect, hybrids can survive for a very long time in streams even after the disappearances there of their parents, as frequently documented for aquatic plants (e.g. Preston et al 1998, Kaplan & Fehrer 2011, Prančl et al 2014, Kaplan et al 2018. Except for putative multiple backcrosses of R. peltatus we recorded two unique cytotypes of unknown origin (upper Vltava river, Czech Republic; Váh river, Slovakia; Table 3), which are both heterophyllous and apparently derived from R. peltatus, forming plentiful populations without the presence of any other Batrachium taxa.…”
Section: Interspecific Hybridizationmentioning
confidence: 89%
“…Due to the heterosis effect, hybrids can survive for a very long time in streams even after the disappearances there of their parents, as frequently documented for aquatic plants (e.g. Preston et al 1998, Kaplan & Fehrer 2011, Prančl et al 2014, Kaplan et al 2018. Except for putative multiple backcrosses of R. peltatus we recorded two unique cytotypes of unknown origin (upper Vltava river, Czech Republic; Váh river, Slovakia; Table 3), which are both heterophyllous and apparently derived from R. peltatus, forming plentiful populations without the presence of any other Batrachium taxa.…”
Section: Interspecific Hybridizationmentioning
confidence: 89%
“…Preston et al 1998;Kaplan and Fehrer 2004Kaplan and Uotila 2011). Recently, Kaplan et al (2018) identified a sterile clone of P. pulcher Tuck. × P. oakesianus J.W.Robbins persisting for a long time in Florida, USA, although P. oakesianus currently does not occur in Florida, and its nearest sites are as distant as in Virginia, approximately 1,100 km away.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the application of isozyme electrophoresis (Hollingsworth et al 1995;Fant et al 2001a, b;Kaplan et al 2002;Kaplan and Wolff 2004) and DNA-based techniques (Kaplan and Fehrer 2004Ito et al 2007;Du et al 2009;Zalewska-Gałosz et al 2009) provided unequivocal evidence for the existence of many of the hybrids. In addition, molecular analyses have recently provided insight into the previously unknown parentage of several hybrids Zalewska-Gałosz et al 2018), contributed to the discovery of several entirely new hybrid combinations (Kaplan et al , 2018Zalewska-Gałosz et al 2010;Bobrov et al 2013) and even confirmed the existence of a natural triple hybrid (Kaplan and Fehrer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…naftolskyi typically grows in vernal pools and has never been found in running water (Lansdown & al., 2017). On the other hand, rivers and streams often provide shelter for rare and sterile hybrids that can spread and persist here even for thousands of years through vegetative propagation (e.g., King & al., 2001; Kaplan & Fehrer, 2009, 2011; Kaplan & al., 2018b; Prančl & al., 2018).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%